The Role of the Diabetes Nurse in the Diabetic Foot Care Room - Jurgita Svirbutaitė; Agata Komar; Lina Valčiukienė; Alma Paškevičė; Erika Sorakienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. As the incidence of diabetes rises rapidly around the world, so does the number of associated complications that require skilled and complex nursing care.